The Role of Technology in Human Resource Development for Sustainability: A Literature Review on Digital Innovation - Mardikaningsih, Rahayu; Wardoyo , Dewie Trie Wijayanti (Bulletin of Science, Technology and Society, 2024)
Digital transformation has become a key driver in human resource (HR) development in the modern era. This process involves the integration of digital technologies into all aspects of an organization's operations, which changes the way business is conducted and affects employee skills and competencies. Digital tools and platforms, such as e-learning and mobile applications, have proven effective for improving training accessibility and employee engagement. Digital innovation contributes to sustainability in HR development by creating a more efficient and environmentally friendly training system. Although challenges in the implementation of digital innovations remain, such as resistance to change, the opportunities to improve HR adaptability are immense. In the future, effective leadership and strategies that support continuous learning will be key to managing the changes generated by digital innovation. With the right approach, organizations can harness the full potential of digital transformation to achieve sustainable HR development.